Manual material handling in the supermarket sector. Part 2: Knee, spine and shoulder joint reaction forces. (April 2021) - Skals, Sebastian; Bláfoss, Rúni; Andersen, Lars Louis; Andersen, Michael Skipper; de Zee, Mark
Abstract: Manual material handling is common in supermarkets and may be a contributing factor to the high prevalence of work-related musculoskeletal disorders, particularly to the lower back. This cross-sectional study applied state-of-the-art musculoskeletal models driven by kinematic data obtained in two supermarkets to estimate joint reaction forces in the knees, shoulders and lumbar spine under dynamic lifting conditions. Based on 1479 lifts from 15 workers, 8 tasks for which the compression or shear forces in the L5-S1 joint exceeded well-known biomechanical tolerance limits were identified. High shoulder forces were associated with lifting relatively heavy merchandise to high shelves, while the weight of the handled merchandise was the main predictor of high knee forces. The study addressed well-known limitations associated with traditional lifting analysis tools and was the first to present a detailed analysis of the biomechanical loads during manual material handling tasks in the supermarket sector based on field measurements. Highlights: Biomechanical field analysis of common handling activities in two supermarkets. Musculoskeletal models were used to estimate 3D dynamic joint reaction forces. Spinal forces exceeded tolerance limits for several manual handling tasks. Boxes of bananas (20.2 kg) and milk crates (17.3 kg) should not be handled manually. Bread (7.9 kg) and cucumbers (10.2 kg) should not be lifted to shoulder level.